Estimation of tree biomass, measurement uncertainties, and morphological topology of Androstachys Johnsonii prain - Magalhaes, Tarquinio Mateus (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD (For))--Stellenbosch University, 2016.